Effect mechanism of nutrients on pathogenic bacteria at the sediment-water interface in eutrophic water - Wen, Sun; Yang, Zhang; Biao, Peng; Jing, Wang (Frontiers in Environmental Science, 2024)
This research analyzed the structure of microbial groups in the sediment-water interface (SWI) and the relationship between the gene expression levels of two typical pathogenic bacteria (Escherichia coli and Enterococcus) and nutrients by using modern biology techniques. The distribution of nutrient content at the SWI mainly showed that nutrient content was significantly greater in the sediment than in the overlying water body. The release flux calculated in accordance with Fick's first law indicated that PO4 3--P in the upper reaches of the reservoir was deposited from the overlying water. The release rate, in addition to sedimentation, of NH4 + -N was significantly greater than that of PO4 3-P. Community structure was mainly dominated by three genera: Methyloparacoccus, Methylomonas, and Arenimonas. The abundances of E. coli and Enterococcus were higher in the surface sediment than in the overlying water body. Pearson correlation analysis showed that in the SWI, E. coli had a significant positive correlation with TN (P < 0.05) and TP (P < 0.05), whereas Enterococcus had a very significant positive correlation with TN and TP (P < 0.01).Key words：Sediment-water interface, Nutrients, Pathogenic bacteria, CorrelationEutrophication in closed water bodies, such as lakes and reservoirs, has become a pollution